The effect of water soluble pentosanes on baking properties of winter rye - E. N. Shabolkina; A. A. Bisharev; N. V. Anisimkina; M. V. Belyaeva (Зерновое хозяйство России)
Currently the research aimed to improve nutritional value and quality of rye bakery products to meet customers' needs is of great urgency. The baking traits of rye flour, the structural and mechanical characteristics of the dough (viscous and rheological) depend on the content of non-starch polysaccharides (pentosanes) namely, their water-soluble part. The purpose of our research is to assess correlation between water-soluble pentosanes in winter rye kernels and kernel weight and to establish the effect of this indicator on the baking parameters of rye flour, i. e. viscosity of water-flour suspension and bread yield. The objects of research were winter rye varieties and promising lines. The content of non-starch polysaccharides in winter rye grain throughout the years of research slightly varied depending on the variety and weather conditions. In 2016 and 2017 the winter rye variety “Roksana” and the line “GK-90” formed high rates of 2.74-2.90%, the variety “Prezent” showed a low value of this characteristic. Estimation of the variation coefficients showed that non-starch polysaccharides influence by genotypic and environmental factors are characterized by low variability CVf = 8.2%. The experiments confirm that when baking rye bread, water-soluble pentosanes perform the following functions: they absorb water, increase the viscosity of the dough, and improve the dimensional stability of bread. There was established a significant correlation between the content of water-soluble pentosanes and grain weight under the conditions of the years 2016 (r = -0.90*) and 2017 (r = -0.88**). It was found that for the years of research, this trait did not correlate with the viscosity of the water-flour suspension, but was significantly associated with bread yield (r = 0.46*). Low enzymatic activity in the studied rye varieties in 2016 and 2017 affected the baking advantages of winter rye. The maximum bread yield was 510-575 cm3, the minimum bread yield was 470-485 cm3. There was also the greatest number of non-starch polysaccharides in kernels during these years.